Diagnosis and Management of Cerebrospinal Fluid Leak in a Panfacial Fracture - Mulinari-Santos, Gabriel [UNESP]; Bonardi, João Paulo [UNESP]; Pires, Willian Ricardo [UNESP]; Jacob, Ricardo Garcia Mureb [UNESP]; De Souza Batista, Fábio Roberto [UNESP]; Faverani, Leonardo Perez [UNESP]; Souza, Francisley Ávila [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP] (Wolters Kluwer, 2017)
Cerebrospinal fluid fistula caused by head trauma is a potentially dangerous problem and precise localization and radical treatment are necessary. We present a case of a patient with Panfacial fracture caused by a motorcycle accident, resulting in a cerebrospinal fluid leakage. The correct diagnosis was realized by computed tomography and auxiliary tests. The successful treatment can be confirmed with the support of radionuclide cisternography examination.
Keywords: Cerebrospinal fluid fistula; cisternography; head trauma